2010
DOI: 10.2308/0148-4184.37.2.39
|View full text |Cite
|
Sign up to set email alerts
|

Accounting and Financial Reporting by a Late 18th Century American Charity

Abstract: Empirical research to date has neglected accounting and external financial reporting among 18th century American charitable institutions. Contemporary understanding of 18th century American practices is supported by evidence relating to commercial transactions primarily among colonial merchants. Our study examines the accounting and financial reporting of the Charleston Orphan House, the first municipal orphanage in America, from its inception in 1790 through its first five years of operations. The institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Financial statements contained in annual reports traditionally represent a vehicle by which an organization’s accountability is demonstrated to its stakeholders (Unerman, 2000), and have a high degree of credibility (Tilt, 1994). Financial reports have been historically noted as legitimizing the activities of organizations (Irvine, 2002; Daniels et al, 2010; Normand and Wootton, 2010). Napier (2002) also notes that it is fundamental that financial statements do indeed stand in some relationship to real transactions and events.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial statements contained in annual reports traditionally represent a vehicle by which an organization’s accountability is demonstrated to its stakeholders (Unerman, 2000), and have a high degree of credibility (Tilt, 1994). Financial reports have been historically noted as legitimizing the activities of organizations (Irvine, 2002; Daniels et al, 2010; Normand and Wootton, 2010). Napier (2002) also notes that it is fundamental that financial statements do indeed stand in some relationship to real transactions and events.…”
Section: Methodsmentioning
confidence: 99%
“…Such means of legitimation were especially important for newly created organizations, which could not rely on a history of sound practice to convince donors of their reliability. Daniels et al (2010) examine the accounting and financial reporting of the Charleston Orphan House from 1790 to 1795 and conclude that accounting and external reporting may have been legitimizing factors to overcome the liability of newness by promoting a sense of transparency among benefactors.…”
Section: Institutional Legitimacy and Isomorphismmentioning
confidence: 99%
“…4 The connection between LG and other local bodies, particularly EIs, is the subject of this study in light of the important role of accounting and accountability ‘in the administration and governance of such organizations and, consequently, in the process of ordering activities within local communities’ (Gomes and Sargiacomo, 2013: 439). In particular, this study focusses on the accounting interrelationship between LGs and non-business and non-governmental associations, which resulted from citizens’ efforts to improve state and LG operations (Daniels et al, 2010; Pridgen and Flesher, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is to demonstrate the accountability of reporting entities. Daniels, Braswell, and Beeler (2010) examined the accounting and financial reporting of orphanage in America. It was found that the orphanage recorded the reporting of expenditure and source of funds.…”
Section: Governance Motivesmentioning
confidence: 99%